Qualimetrical analysis of the technical level of safety couplings - Гутиря, Сергій Семенович; Яглінський, Віктор Петрович (Technology audit and production reserves, 2014)
Establishment of system of indicators of quality and optimum design of the ball safety couplings (BSC) on the basis of scientifically reasonable criteria is an actual scientific and practical problem and a necessary condition for advance of the corresponding production of mechanical engineering of national producers to the world markets. The purpose of the conducted researches is increase of a technical level of designs of BSC by a way of application of the qualimetrical models providing objective, multilevel and system display of their working properties. On the basis of the theory of system qualimetrical modeling fulfilled by authors on standard samples of a batch production of machine- and machine-tool building (gear and worm reducers, friction gears and dynamic vibroquenchers, industrial robots and platforms, etc.), research of a set of working properties of BSC is executed. According to the allocated structurally functional modules of a standard design of BSC, each of which is coordinated with a certain level of hierarchy of the BSC qualimetrical model, indicators of quality are ordered and the corresponding settlement dependences are established. As a result of structurally functional modeling of a standard design of the BSC it is created a matrix of indicators of its reliability, accuracy, load ability and functionality. Normalization of single indicators of quality is executed, created a matrix of quality of qualimetrical model by which the system indicator of a technical level and reserves for optimization of the studied designs are defined.